Engaging And Applying New Communication Technology: A Case Study Of The Usage Of Internet As A Search Practice Among Bernama Journalists - Mohamed, Ramli; Khalib, Aini Hayati (Universiti Sains Malaysia, 2006)
Given the scenario of change within the journalism profession vis-à-vis new communication technology, how does the Malaysian journalism industry cope and adapt to this change? More specifically (i) how do Malaysian journalists find information on the Internet and what are their favourite search engines for information/news gathering? (ii) What are the characteristics of the Internet that influence journalists’ search practices? (iii) What is the attitude of journalists towards Internet usage in their day-to-day work and what are the perceived successes and failures of the Internet as a source of information? (iv) What is the level of knowledge they possess in terms of technology, in general, and the Internet in particular? This article attempts at finding answers to the above questions in an effort to examine the impact of new media, the Internet in particular, from the standpoint of the diffusion of Internet usage among journalists, especially with their preference for search engines, search practices, search tools, websites and web-based technologies.